2021
DOI: 10.1002/1873-3468.14041
|View full text |Cite
|
Sign up to set email alerts
|

The endolysosomal adaptor PLEKHM1 is a direct target for both mTOR and MAPK pathways

Abstract: The lysosome is a cellular signalling hub at the point of convergence of endocytic and autophagic pathways, where the contents are degraded and recycled. Pleckstrin homology domain‐containing family member 1 (PLEKHM1) acts as an adaptor to facilitate the fusion of endocytic and autophagic vesicles with the lysosome. However, it is unclear how PLEKHM1 function at the lysosome is controlled. Herein, we show that PLEKHM1 coprecipitates with, and is directly phosphorylated by, mTOR. Using a phosphospecific antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 60 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…Recent evidence has suggested that PLEKHM1 is directly phosphorylated by mTOR and Erk2 MAPK 17 at Ser432/Ser435, while TMEM55B undergoes Erk-dependent phosphorylation in RAW 264.7 macrophages treated with Toll-like receptor ligands 8 . In addition, it is well-established that p38, JNK and Erk1/2 MAPK get strongly activated in response to oxidative stress 18 .…”
Section: Resultsmentioning
confidence: 99%
“…Recent evidence has suggested that PLEKHM1 is directly phosphorylated by mTOR and Erk2 MAPK 17 at Ser432/Ser435, while TMEM55B undergoes Erk-dependent phosphorylation in RAW 264.7 macrophages treated with Toll-like receptor ligands 8 . In addition, it is well-established that p38, JNK and Erk1/2 MAPK get strongly activated in response to oxidative stress 18 .…”
Section: Resultsmentioning
confidence: 99%